INTELLECTUAL CAPITAL, INSTITUSIONAL OWNERSHIP, PROFITABILITAS PADA FINANCIAL AWARENESS DENGAN CASH FLOW VOLATILITY SEBAGAI VARIABEL INTERVENING - Eri Kusnanto; Ngadi Permana; Grace Yulianti (Universitas Pendidikan Ganesha, 2022)
This research aims to examine the effect of intellectual capital, institutional ownership and profitability on financial awareness with cash flow volatility as an intervening variable. Testing research data using a panel data regression model. The population used in this study were all consumer goods companies listed on the Indonesia Stock Exchange from 2015-2019, with purposive sampling method obtained 29 samples of company data with 145 tests for 5 years. The results show that intellectual capital and profitability affect financial awareness while institutional ownership and cash flow volatility do not directly affect financial awareness, but after testing the intervening variable shows that cash flow volatility does not affect intervening between institutional ownership and financial awareness